Norma Politik dan Bantuan Multilateral: Strategi Jepang dalam Mengatasi Covid-19 di Indonesia - Tursina, Zahidiyah Ela; Soesilowati, Sartika; Susanto, Siti Rochmawati (Intermestic: Journal of International Studies, 2023)
This paper explains how political norms can influence Japan to use multilteral assistance strategy in the contextof dealing with Covid-19 in Indonesia. Japan distributes Official Development Assistance (ODA) asssitance through a multilateral assistance strategy because Japan, as an Organization for Economic Co-operation and Development (OECD) country, follows international norms, namely the 2008 Accra Agenda for Actions norms. These international norms use the principle of inclusive partnership in efforts to provide help. These international norms are strongly supported by domestic norms, namely the 2015 Development Cooperation Charter. The charter adhers the principle of development cooperation in efforts to provide assistance. The norms that contain the values the principle of cooperation internalized into the policy of providing Japanese ODA assistance, namely in the form of Japan's multilateral assistance strategy in the context of handling Covid-19 in Indonesia.